Accessibility and retrieval of national information in Nigerian university libraries (2011)
This paper sets out to examine the accessibility, retrieval and use of Publications Ordinance (PO) materials in Nigerian university libraries using Kenneth Dike Library (KDL) as a case study. The survey research design was adopted and a structured questionnaire was distributed to 400 users comprising students, staff and external users. The records of the use of PO materials between October 2009 and September 2010 were also perused. Result shows that majority of users are aware of the availability and importance of legal deposits collection in the library but have difficulty in retrieving the materials due to inability to have direct physical contact with the materials. The study therefore proffers that Nigerian university libraries should, as a matter of urgency, organize PO collections and adopt a harmonized library management system in order to enhance users’ access and retrieval of the materials.